The effects of swimming and running on energy intake during 2 hours of recovery - Lambert, C. P.; Flynn, M. G.; Braun, W. A.; Boardley, D. J. (The Journal of Sports Medicine and Physical Fitness, 1999)
OBJECTIVE: To determine energy intake in the 2 hrs after swimming (S) and running (R) at the same relative exercise intensity and duration (71.8 +/- 2.5% VO2max; 45 min) to evaluate whether a difference in recovery energy intake could explain the greater body fat observed in swimmers relative to runners. METHODS: Experimental design: this was a randomized crossover design. Setting: running exercise was conducted on a motorized treadmill (Quinton) while swimming was conducted in a 45.7 m pool. Participants: eight well-trained competitive male triathletes participated in this investigation. Interventions: subjects were blinded to the purpose of the study and swam and ran on separate occasions for 45 min at 71.8 +/- 2.5% of VO2max. Subjects were then placed in a room with a variety of foods and beverages for 2 hrs after R and S. Measures: energy intake (kJ/2 hrs and kcal/2 hrs) was determined by weighing and measuring the food remaining in the room after 2 hrs of postexercise recovery. Expired gases, heart rates, and Ratings of Perceived Exertion were obtained at 15 min intervals throughout exercise. Blood samples for serum glucose and lactate were obtained preexercise and immediately, 15 min, and 135 min postexercise. Perceived hunger and thirst ratings were obtained after the subjects were seated in the room containing the food. RESULTS: Serum glucose was significantly (p < or = 0.05) higher after R compared to S immediately after exercise (5.4 +/- 0.3 mmol/L for R and 4.2 +/- 0.1 mmol/L for S) but no significant differences were observed for hunger using a five point Likert scale (3.3 +/- 0.3 for R and 3.4 +/- 0.3 for S), energy intake (4584 +/- 611 kJ/2 hrs; 1095 +/- 146 kcal/2 hrs for R and 4383 +/- 484 kJ/2 hrs; 1047 +/- 116 kcal for S) or blood lactate. CONCLUSION: The type of exercise, swimming or running, did not significantly influence energy intake during 2 hours of postexercise recovery.